Navy Chapel Area - Location of Headstones & Graves Patuxent River, Maryland (1943) - Cook (Navy Department, Bureau of Yards and Docks Naval Air Station, Patuxent River, MD, 1943)
Shows locations of graves in surrounding the chapel at NAS Patuxent River. Graves marked with a number which is keyed to second sheet (not scanned)